The risk of children's malnutrition amid COVID-19 pandemic: A literature review - Lestari Octavia; Sri Wulan Windu Ratih (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Malnutrition is one of the public health problems that existed during the pandemic; both problems, under and overnutrition, existed. Furthermore, malnutrition can worsen the infection in all groups, including children. The risk of being infected was higher in the malnutrition group than in the well-nourished one. This article aimed to review the risk of malnutrition and possibly related factors in children during the pandemic. This article used the literature review method and was conducted by the initial 2022 from several countries. The object included in the analysis was children's health and nutrition related. The source of articles highlighted the occurrence of malnutrition in children. The source of articles was from PubMed and Cochrane Library, which resulted in 21 eligible papers. The result of the study found that the identified possible factors are self-isolation, physical activity, dietary patterns, nutrient shortage, and socioeconomic factors. There was a shift in dietary patterns among children during the COVID-19 pandemic due to several factors. Those are the scarcity of food sources and compensation for the lockdown, and those findings confirmed the possibility of under- and overnutrition among children. In low-middle income countries (LMICs), the risk of malnutrition problems in this pandemic has heightened the magnitude of the public health problem. The mitigation program should overcome the existing problem to minimize the adverse effect of malnutrition among children.